A successfully stress-forecast earthquake - Crampin, Stuart; Volti, Theodora; Stefánsson, Ragnar (Geophysical Journal International, 1999)
A M = 5 earthquake in Iceland has been successfully ‘stress forecast’ by using variations in time delays of seismic shear wave splitting to assess the time and magnitude at which stress-modified microcracking reaches fracture criticality within the stressed volume where strain is released. Local investigations suggested the approximate location of the forecast earthquake. We report the criteria on which this stress forecast was based.